Geochemical Characteristics and Gas Source Contributions of Noble Gases of the Sulige Large Tight Gas Field of Upper Paleozoic in Ordos Basin, China - Xiaobo, Wang; Lianhua, Hou; Jian, Li; Chunxia, Yang; Liyong, Fan; Jianfa, Chen; Chunlin, Zhang; Jianying, Guo; Jixian, Tian; Yue, Zheng; Chunlong, Yang (Frontiers in Earth Science, 2022)
Tight gas is the fastest developing unconventional natural gas resources, becoming the principal part for gas reserves and production growth in China. The Sulige gas field is the largest gas field and also typical low porosity and low permeability tight sandstone gas field discovered in China，with annual natural gas output exceeding 300 billion and cumulative output exceeding 290 billion, playing an important role in ensuring national energy provision, helping China's energy transformation and promoting green, low-carbon, environmental protection and high-quality development. Based on sample collecting and laboratory analyzing, natural gas compositions including hydrocarbons, non-hydrocarbons, light hydrocarbons and noble gases of Sulige gas field are systematically analyzed, their genetic identifications are identified, and finally gas source originations and contribution proportions are comprehensively discussed from the perspectives of noble gases and hydrocarbon gases. The main achievements are as follows: (1) Natural gases in Sulige gas field are mainly alkane gases, with high methane content, high drying coefficient, low heavy hydrocarbon contents, low non-hydrocarbon gas contents of CO2 and N2, and relatively low noble gas contents. The helium content is relative 2 order of magnitude higher than atmospheric value, while neon, argon, krypton and xenon are relative about 1~2 orders of magnitudes lower than atmospheric values. (2) The carbon and hydrogen isotopes of alkanes are generally positive sequence distributions with some part inversion. The 3He/4He values is mainly distributed in magnitude of 10-8,the 40Ar/36Ar is ranged from 506 to 1940，the 129Xe is relative loss and the 132Xe is relative surplus. (3) Natural gases in Sulige gas field are typical coal formed gas generated from humic organic mother material with maturity from mature to high mature according to a C7 and C8 light hydrocarbons and alkane carbon isotopes. Noble gases are typical crustal genesis, mainly originating from the radioactive decay of crustal source materials. (4) The gas-source correlations of noble gases and alkane gases and their quantitative evaluations on source contributions show that natural gases in Sulige gas field are originated from Carboniferous-Permian coal measure source rocks in Ordos Basin, mainly contributed by coals and supplemented by mudstones, accounting for 55-60% and 40-45% separately.